Implementasi Metode UMMI untuk Meningkatkan Kemampuan Bacaan Al-Quran Siswa di SMPIT Anni’mah Margahayu - Delfi Fajriani (Jurnal Pendidikan Islam Indonesia, 2019)
Today many schools are based on Islam that is quality oriented. One guarantee of the quality their graduates in guardian students is the ability to read al-Quran well in every child. However, the current phenomenon is a lack of improvement in learning it especially in reading al-Quran in several schools. The UMMI method helps institutions and teachers improve the ability to process Qur'anic learning that is effective, easy, fun and touching. This study uses a quasi-experimental method, using the quasi experimental design; the instruments used are observation, interviews, direct tests and documentation. The research was carried out in MIPA VIIIT class VII of Anni'mah Margahayu as the experimental class and class VII A of Muhammadiyah Margahayu as a control class with UMMI teacher subjects and 25 students in each class. Based on the results of the analysis of the Paired Test T-test samples in the experimental class that were treated with learning using the UMMI method, it is known that the sig value. (2-tailed) of 0,000 <0,05. Because the sig value. (2-tailed) 0,000 smaller than 0.05, it can be concluded that the use of the UMMI method in the experimental class can improve students' Koran reading abilities.